2000
DOI: 10.1002/(sici)1096-9888(200002)35:2<178::aid-jms927>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

High‐energy collision‐induced dissociation of small polycyclic aromatic hydrocarbons

Abstract: High-energy collision-induced dissociation (CID) experiments on polycyclic aromatic hydrocarbons (PAHs)having 2-6 rings, naphthalene, anthracene, phenanthrene, fluoranthene, pyrene and coronene, were performed, and the relative abundances of their fragment ions were investigated as a function of collision energy. The results revealed that the PAHs except naphthalene showed a bimodal-type distribution of positive fragmentation ions, which is closely similar to the fragment-ion distribution reported for the CID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Increasing the collision energy leads to enhanced fragmentation, successive fragments resulting from the neutral loss by elimination of hydrocarbons and complex structural rearrangements. As observed by Arakawa et al 23, as well as with the collision induced dissociation (CID) of C 60 + and C 70 + fullerene24, the mass fragmentation distribution becomes bimodal when the collision energy reaches a certain level. This threshold varies with the PAH studied.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Increasing the collision energy leads to enhanced fragmentation, successive fragments resulting from the neutral loss by elimination of hydrocarbons and complex structural rearrangements. As observed by Arakawa et al 23, as well as with the collision induced dissociation (CID) of C 60 + and C 70 + fullerene24, the mass fragmentation distribution becomes bimodal when the collision energy reaches a certain level. This threshold varies with the PAH studied.…”
Section: Resultsmentioning
confidence: 80%
“…Arakawa et al reported recently23 some results of PAHs fragmentation obtained by electron ionisation (EI) and using a high‐energy collision cell on a magnetic electrostatic analyses (BE‐type) double focusing mass spectrometer, where they investigated the differentiation of isomers. The results presented here show that, using charge transfer from tropylium post‐column derivatisation, the comparatively soft ESI technique provides enough internal energy to the precursor ions to initiate fragmentation in the collision cell of a tandem quadrupole mass spectrometer and could therefore be used to differentiate isomers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations